ОПТИМИЗАЦИЯ ДИАГНОСТИКИ ПРОЛАПСА МИТРАЛЬНОГО КЛАПАНА И ОСОБЕННОСТИ ЕГО ТЕЧЕНИЯ В ДЕТСКОМ ВОЗРАСТЕ - Г. М. Кульниязова; С. Г. Давидович; А. Н. Сейпенова; Ф. С. Саулеева (SINAPS LLC, 2015)
Purpose of investigation. To study the effectiveness of a modifi ed method of mitral valve prolapse diagnosis and its fl ow dynamics in children in terms of time (10-15 years old).Materials and methods. 75 children in age of 3-18 years old with undifferentiated connective tissue dysplasia and also with incorporation of modifi ed method of mitral valve prolapse diagnosis were examined and its evolution in 30 adult patients (average age is 27,5years old) was studied together with the diagnosis, established 10-15 years ago.Results. The mitral valve prolapse in 30,7 % of children with undifferentiated connective tissue dysplasia at rest is "dumb". It was established, in terms of time that is in adulthood, mitral valve prolapse is characterized by progression of clinical and echocardiographic parameters.Conclusion. The study showed the diagnostic value of the optimized method for the diagnosis of mitral valve prolapse in children with undifferentiated connective tissue dysplasia, providing its preclinical diagnosis. Stressed functioning of the cardiovascular system in patients with mitral valve prolapse, in adulthood, dictate the need for timely correction of the daily routine, reasonable therapy, reasoned and controlled exercises to be done.